The Role of Social Marketing in Supporting Sustainability Marketing - Moh Samsul Arifin; I Wayan Gede Antok Setiawan Jodi; Edi Arisandi; Tengku Kespandiar; Elizabeth Elizabeth (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
Technological developments have given rise to many new types of marketing. One of these is sustainable marketing. Sustainable marketing is not just about selling products or services, but also about how those products or services are developed, produced, and distributed in a responsible and sustainable manner. The purpose of this research is to understand the role of social marketing in supporting sustainability marketing. The research analysis in this study employed a descriptive theoretical approach. To support the theoretical explanations in this study, secondary data was obtained from books, e-books, and other relevant sources as reference materials. The research findings indicate that the role of social marketing in supporting sustainability marketing can shift consumer behavior toward a more pro-environmental and pro-social direction, increase awareness of sustainability issues, create long-term socio-economic value, and strengthen business commitment to sustainable development goals.